The effects of tea plant age on the color, taste, and chemical characteristics of Yunnan Congou black tea by multi-spectral omics insight - Piaopiao Long; Shengxiao Su; Zisheng Han; Daniel Granato; Wei Hu; Jiaping Ke; Liang Zhang (Food Chemistry: X, 2024)
The present study comprehensively used integrated multi-spectral omics combined with sensory evaluation analysis to investigate the quality of three types of Yunnan Congou black teas from different tree ages (decades, DB; hundreds, HB; a thousand years, TB). TB infusion presented the highest scores of sweetness and umami, higher brightness, and yellow hue. Eighty-four marker metabolites were identified, including Amadori rearrangement products, catechin oxidation products, flavonoid glycosides, and organic acids, which are simultaneously related to tea infusions' color and taste. Moreover, the content of some characteristic flavonoid glycosides and organic acids was determined. Our finding implied trans-4-O-p-coumaroylquinic acid and quercetin 3-O-rutinoside contributed to bitterness and astringency, while dehydro theanine-glucose Amadori product and xylopyranosyl-glucopyranose resulted in umami and sweetness. These results provided quantitative and qualitative information for deciphering differences among black teas with different tea plant ages, conducing to the further utilization of ancient tea plants in Southwest China.